Human Persecution is An Important Threat to the Conservation of the Endangered Black-and-Chestnut Eagle in Northern Andes - Restrepo Cardona, Juan Sebastián (2023)
Background and Research Aims: The Black-and-chestnut Eagle (Spizaetus isidori) has a total population of fewer than 1000 adult individuals, and is categorized as Endangered at the global level. The northern Andes (Ecuador and Colombia) represent one of the last population strongholds of the species. In this study, we analyzed human persecution of the Black-and-chestnut Eagle as retaliation or as a preventive measure against poultry predation, as well as other threats that have affected the species in this geographical region between 2000 and 2022. Methods: In order to understand the human persecution and other threats faced by the Black-and-chestnut Eagle in the northern Andes, we compiled records of immature and adult individuals of the species that had been shot, captured, or had presented evidence of any other affectations during the last 23 years. Results: We found a total of 96 Black-and-chestnut Eagles affected by different threats. Human persecution of the species to prevent poultry predation was the motive in 81% (46 of 57) of the cases of shot eagles, 67% (10 of 15) of those captured illegally, 30% (3 of 10) of those in which the cause of affectation was undetermined and for one individual that had been stabbed. Immature eagles were more affected than adult eagles by human persecution. Black-and-chestnut Eagles were also affected by electrocution, illegal trafficking and collision with vehicle. Conclusion: Human persecution as retaliation or as a preventive measure against poultry predation is an important threat to the conservation of the Black-and-chestnut Eagle in northern Andes. Implications for Conservation: Strict application of laws at human persecution sites, identification and monitoring of areas with high risk of human-eagle conflict, development of environmental educational programs, strengthening of the technical capacities of rural communities, maintaining or even increasing forest cover, and reducing the exposure of poultry by using enclosures are key for Black-and-chestnut Eagle conservation in the northern Andes.